Nursing and Health Sciences Students' Perspective on the Functions of Academic Advising - Khalid A. Aljohani PhD, RN; Abdulaziz Mofdy Almarwani PhD, RN; Ahmad Tubaishat PhD, RN; Paul Reinald B. Gracia PhD, RN; Maria Jocelyn B. Natividad PhD, RN; Helen M. Gamboa PhD, RN; Mohammed S. Aljohani PhD, RN (SAGE Publishing, 2023)
Introduction Nursing and allied health students represent a significant percentage of undergraduate students. Academic advising is integral to students' success. Objective This study aimed to identify nursing and allied-health science students' perspectives on academic advising functions and identify the demographic factors associated with these perspectives. Methods A cross-sectional, correlational study was conducted with 252 students who completed a survey on students' perspectives on academic advising functions. Students were recruited from a large public university in western Saudi Arabia. Results The results revealed that 97.6% of students reported knowing their academic advisor and 80.8% reported meeting with their advisor at least once over the past year. Overall, students perceived academic advising as important ( M  = 4.0, SD ± 0.86). The social role of academic advising was perceived as its most important function ( M  = 4.1, SD ± 0.85), followed by the academic role ( M  = 4.0, SD ± 0.87) and the personal role ( M  = 3.9, SD ± 0.87). The results showed that junior students perceived academic advising as more important than their counterparts. There was a weak significant correlation between students' perception of academic advising functions and the number of meetings held with their advisors. Conclusion Faculty should improve students' understanding of the academic advisor's role in academic progress. Students understanding of their academic advisor's role in supporting their academic progress should be emphasized, especially among senior students.